BOOK REVIEW: Jana Osterkamp (Hg.), “Kooperatives Imperium. Politische Zusammenarbeit in der späten Habsburgermonarchie”, München, Vandenhoeck & Ruprecht, 2018, 336 p., ISBN: 978-3-525-37069-8 - POPESCU, Luminiţa (Studia Universitatis Babeș-Bolyai Historia, 2018)
The volume Kooperatives Imperium. Politische Zusammenarbeit in der späten Habsburgermonarchie, recently edited by Jana Osterkamp, brings together a series of scientific papers presented at the Conference organized by the Collegium Carolinum and the Masarykův ústav a Archiv AV ČR held in Bad Wiessee from 10 to 13 November 2016, and which had as its central point the highlighting of the internal cooperative tendencies and processes within the Habsburg Monarchy. Jana Osterkamp is an historian and researcher within the Collegium Carolinum, her fields of interest being the political, social and imperial history of the Habsburg Monarchy, the history of federalism in Central and Eastern Europe, as well as constitutional history in Czechoslovakia.